A Direct Method to Access Substituted Pyreno[4, 5‐c:9, 10‐c′] difuran and its Analogues. Issue 11 (26th April 2018) - Chen, Wangqiao; Long, Guankui; Kanehira, Koji; Zhang, Mingtao; Michinobu, Tsuyoshi; Liu, Ming; Zhang, Qichun
Abstract: In this research, pyreno[4, 5‐c:9, 10‐c′]difuran and its analogues have been successfully synthesized through a one‐step reaction using the same precursor and their physicochemical properties were studied. UV/Vis, fluorescence and CV measurements illustrated that the inserted chalcogen atoms (O, S and Se) brought almost no change on the photochemical and electrochemical properties whereasTM‐2N‐CH3 exhibited more blue‐shifted fluorescence emission and simultaneously elevated HOMO energy level. Abstract : O can be replaced by S, Se, and NCH3 too ! Pyreno[4, 5‐c:9, 10‐c′]difuran and its analogues have been successfully synthesized through a one‐step reaction using the same precursor and their physicochemical properties were also studied. UV/Vis, fluorescence and CV measurements showed that the inserted chalcogen atoms (O, S and Se) brought almost no change on the photochemical and electrochemical properties whereasTM‐2N‐CH3 (see Scheme) exhibited more blue‐shifted fluorescence emission and simultaneously elevated HOMO energy level.